Building an optimal portfolio - Case Study - hakim mohsin mohammad; layla mohsin hassan (Iraqi Journal for Administrative Sciences, 2024)
The Present Study Tries to Show the phases of the investment portfolio which took important place in investment studies , and took various shapes and forms . This requires specification of its elements and types , focusing on some of these types which have specific importance in investment . The importance of the study springs from financial and economic variables which the world economy witnessed by way of increasing capital flow in investment in finance markets . This can all be achieved through investment institutions , saving boxes , the development of financial , nonfinancial and banking institutions , taking care of getting fast profits and being away of risks .